Relationship between reactive strength index variants in rugby league players - McMahon, J. J.; Suchomel, T. J.; Lake, J. P.; Comfort, P. (The Journal of Strength and Conditioning Research, 2021)
Two reactive strength index (RSI) variants exist, the RSI and RSI modified (RSImod), which are typically calculated during the drop jump (DJ) and countermovement jump (CMJ), respectively. Both RSI variants have been used to monitor athletes' ability to complete stretch-shortening cycle actions quickly, but they have never been compared. The purpose of this study was to determine whether they yield relatable information about reactive strength characteristics. Male professional rugby league players (n = 21, age = 20.8 ± 2.3 years, height = 1.82 ± 0.06 m and body mass = 94.3 ± 8.4 kg) performed 3 DJs (30 cm) and CMJs on a force plate. Reactive strength index and RSImod were subsequently calculated by dividing jump height (JH) by ground contact time (GCT) and time to take-off (TTT), respectively. All variables were highly reliable (intraclass correlation coefficient =0.78) with acceptable levels of variability (coefficient of variation =8.2%), albeit larger variability was noted for DJ variables. Moreover, there was a large relationship between RSI and RSImod (r = 0.524, p = 0.007), whereas very large relationships were noted between JHs (r = 0.762, p < 0.001) and between GCT and TTT (Rho = 0.705, p < 0.001). In addition, RSI (0.90 ± 0.22) was largely and significantly (d = 2.57, p < 0.001) greater than RSImod (0.47 ± 0.08). The DJ-derived RSI yields much larger values than the CMJ-derived RSImod and although a large relationship was noted between them, it equated to just 22% shared variance. These results suggest that the 2 RSI variants do not explain each other well, indicating that they do not assess entirely the same reactive strength qualities and should not be used interchangeably.